1967
DOI: 10.1039/j39670000510
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenoid constituents of rose-bay willow-herb

Abstract: The leaves of rose-bay willow-herb (Chamaenerion angustifolium) are shown to contain ursolic acid, oleanolic acid, maslinic acid, and a hitherto unknown acid, 2a-hydroxyursolic acid. A partial synthesis of the new acid is described and some of its derivatives are compared with the corresponding derivatives of the isomeric maslinic acid.* The compound described by Aplin and co-workers as 2-hydroxyursolic acid (see ref. 6b) was later shown to be maslinic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1968
1968
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Our work on the dichloromethane-methanol extract of the stem bark of E. angolense has resulted in the isolation of ten known compounds: 7α-acetoxydihydronomilin 1 (Ahmed et al, 1978), 7α-obacunylacetate 2 (Bennett and Hasegawa, 1982), methylangolensate 3 (Connolly, 1983), tricosanoic acid 4 (Francis, 1939), 22hydroxyhopan-3-one 5 (Mahato and Kundu, 1994), 24-methylenecycloartenol 6 (Ferreira et al, 2000) (structure to be confirmed), methyloleanate (Glen et al, 1967), betulinic acid (Mahato and Kundu, 1994), β-sitosterol (Furuya et al, 1987) and β-sitosterol-3-O-β-D-glucoglucopyranoside (Sakakibara et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Our work on the dichloromethane-methanol extract of the stem bark of E. angolense has resulted in the isolation of ten known compounds: 7α-acetoxydihydronomilin 1 (Ahmed et al, 1978), 7α-obacunylacetate 2 (Bennett and Hasegawa, 1982), methylangolensate 3 (Connolly, 1983), tricosanoic acid 4 (Francis, 1939), 22hydroxyhopan-3-one 5 (Mahato and Kundu, 1994), 24-methylenecycloartenol 6 (Ferreira et al, 2000) (structure to be confirmed), methyloleanate (Glen et al, 1967), betulinic acid (Mahato and Kundu, 1994), β-sitosterol (Furuya et al, 1987) and β-sitosterol-3-O-β-D-glucoglucopyranoside (Sakakibara et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…The similarity in the chemical shifts of the seven methyl groups in the NMR spectra of the compound and its diacetate suggested the two oxygen functions to be a and a. The formation of an o,o-isopropylidene derivative with acetone supported the cis-configuration or at least a diequatorial conformation [7]. When two hydroxyls are on @-side, the signals of two methyls (24 and 25) would shift to low field in comparison to those of the diacetate in question.…”
Section: Cooch3mentioning
confidence: 92%
“…The method of analysis of the DNA and RNA content of peripheral blood lymphocytes has been described elsewhere (Glen, 1967). It is carried out in two stages.…”
Section: Methodsmentioning
confidence: 99%